VO2max testing in trail runners: Is there a specific exercise test protocol? - Scheer, V.; Ramme, K.; Reinsberger, C.; Heitkamp, H.-C. (International Journal of Sports Medicine, 2018)
Trail running places specific physiological demands on the human body due to its uphill and downhill running sections. We developed and investigated a more sport-specific trail exercise test protocol (inclination and speed incremental protocol), and compared it to two standard exercise test protocols (horizontal step and ramp protocol) in thirteen highly trained trail runners (age 31±6 years, height 179±6.4 cm, weight 69.2±7.9 kg, BMI 21.6±2.1 kg/m2). The maximum oxygen uptake (VO2max) measured during the trail test (62.5±5.9 ml·kg-1·min-1, [95% CI: 59.0-66.1]) was significantly higher compared to both the step test (60.1±5.3 ml·kg-1·min-1, [95% CI: 56.8-63.3], p=0.024) and the ramp test (59.7±5.5 ml·kg-1·min-1, [95% CI: 56.4-63.0], p=0.028). Time to task failure was significantly shorter in the trail test (557±73 s, [95% CI: 512-601]) compared to both the step test (1378±152 s, [95% CI: 1286-1470], p<0.001) and the ramp test (605±95, [95% CI: 547-662], p<0.001). Other physiological measurements obtained were similar. The trail test was the preferred choice in our group of trail runners. This study supports the implementation of the trail test in practice, and recommends that its validity be evaluated further.